Metabolitos secundarios y actividad antioxidante de extractos de Odontadenia macrantha y Euphorbia umbellata - Orbe Tello, Liz Ericka (2025)
Objective: To quantify the content of secondary metabolites and the antioxidant activity present in the extracts of Odontadenia macrantha and Euphorbia umbellata. Methodology: Quantitative analyses were performed using UV-visible spectrophotometric methods to determine the contents of alkaloids and saponins in the bark of O. macrantha, as well as in the leaves and stems of E. umbellata. Antioxidant activity was evaluated using the DPPH test. Results: The results indicated that the bark of O. macrantha had the highest content of alkaloids (28.70 mg/100g) and saponins (247.26 mg/100g). In comparison, the stem of E. umbellata contained 26.10 mg/100g of alkaloids and 249.56 mg/100g of saponins, while the leaves of E. umbellata showed a significantly lower content, with 14.10 mg/100g of alkaloids and 90.68 mg/100g of saponins. In terms of antioxidant activity, the bark of O. macrantha exhibited an IC50 of 7 mg/mL, indicating a strong antioxidant capacity, while the extracts of E. umbellata (both leaves and stem) had an IC50 greater than 40 mg/mL, demonstrating a much weaker activity. Conclusion: This study highlights the potential of O. macrantha as a significant source of alkaloids and saponins, as well as its remarkable antioxidant activity. These findings suggest the viability of this species for future research and applications in the pharmaceutical and nutraceutical industries.